2017
DOI: 10.3347/kjp.2017.55.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Genotyping of Toxoplasma gondii in Brazilian Dogs

Abstract: Strains of Toxoplasma gondii in Brazil are highly genetically diverse compared to strains from North America and Europe. Dogs are epidemiologically important because they act as sentinels for T. gondii infections in humans and are good indicators of environmental contamination. The aim of this study was to isolate and genetically characterize T. gondii strains from tissues of naturally infected Brazilian dogs. For this study, 21 blood samples were collected from dogs at the Zoonosis Control Centers of Ilhéus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…On the top of that, there is a wide genetic diversity within the parasites isolated from asymptomatic dogs (73, 74) and cats (72, 75), corresponding to a complex epidemiology shown in different geographical areas [(76), http://toxodb.org/toxo/].…”
Section: Toxoplasma Gondii Genotype and Clinical Toxoplasmosismentioning
confidence: 99%
“…On the top of that, there is a wide genetic diversity within the parasites isolated from asymptomatic dogs (73, 74) and cats (72, 75), corresponding to a complex epidemiology shown in different geographical areas [(76), http://toxodb.org/toxo/].…”
Section: Toxoplasma Gondii Genotype and Clinical Toxoplasmosismentioning
confidence: 99%
“…This suggests that, while dogs did not prove to be a good indicator of foodborne disease in people, they may be a reliable indicator of environmental infection. Other studies have also concluded that dogs may be used as environmental sentinels [50,51,52]. Results from a study in Ubatuba, São Paulo State [53] utilized dogs as sentinels to demonstrate that toxoplasmosis was linked to sanitary problems (largely cooking of food), rather than the presence of rodents or untreated water.…”
Section: Review Of the Global Literaturementioning
confidence: 99%
“…Some experiments are much more focused on analyzing the correlation between clinical data and biological markers of acute, chronic or secondary infections involving European or North-American strains [27], while others attempt to demonstrate the basic patterns of T. gondii pathophysiological mechanisms using transgenic mice [11, 19, 44] or other advanced technologies, such as bioluminescence imaging [7]. Some general reviews reported data from experimental assays and overviewed hypotheses underlying toxoplasma virulence based on general comparisons between different genotypic strains including the clonal reference ones [18, 21, 35, 50]. Recently, Saraf et al [43], proposed a standardized methodology for future studies in order to enable more efficient and effective analysis of genetics and virulence patterns for T. gondii .…”
Section: Discussionmentioning
confidence: 99%